GID E3 ligase supramolecular chelate assembly configures multipronged ubiquitin targeting of an oligomeric metabolic enzyme - Sherpa, Dawafuti; Chrustowicz, Jakub; Qiao, Shuai; Langlois, Christine R.; Hehl, Laura A.; Gottemukkala, Karthik Varma; Hansen, Fynn M.; Karayel, Ozge; von Gronau, Susanne; Prabu, J. Rajan; Mann, Matthias; Alpi, Arno F.; et al. (Molecular cell, 2021)
How are E3 ubiquitin ligases configured to match substrate quaternary structures? Here, by studying the yeast GID complex (mutation of which causes deficiency in glucose-induced degradation of gluconeogenic enzymes), we discover supramolecular chelate assembly as an E3 ligase strategy for targeting an oligomeric substrate. Cryoelectron microscopy (cryo-EM) structures show that, to bind the tetrameric substrate fructose-1,6-bisphosphatase (Fbp1), two minimally functional GID E3s assemble into the 20-protein Chelator-GIDSR4, which resembles an organometallic supramolecular chelate. The Chelator-GIDSR4 assembly avidly binds multiple Fbp1 degrons so that multiple Fbp1 protomers are simultaneously ubiquitylated at lysines near the allosteric and substrate binding sites. Importantly, key structural and biochemical features, including capacity for supramolecular assembly, are preserved in the human ortholog, the CTLH E3. Based on our integrative structural, biochemical, and cell biological data, we propose that higher-order E3 ligase assembly generally enables multipronged targeting, capable of simultaneously incapacitating multiple protomers and functionalities of oligomeric substrates. [Display omitted] •GID E3 ligase assembly resembles a behemoth organometallic supramolecular chelate•Multipronged targeting of oligomeric structure and metabolic function of substrate•Yeast Gid7, human WDR26, and MKLN1 mediate supramolecular assembly of GID/CTLH E3s•Human CTLH E3 structural and mechanistic features parallel yeast GID E3 ligase Structural, biochemical, and cellular data reveal supramolecular assembly of yeast GID E3 ligase. GID E3 forms a chelate-like structure tailored to target the oligomeric structure and metabolic function of the gluconeogenic enzyme substrate Fbp1. The orthologous human CTLH E3 contains a GID-like core assembly that forms a supramolecular chelate and utilizes a GID-like ubiquitin ligase mechanism.